Application of Lean Six Sigma, FMEA and Fuzzy to Improve Garment Product Quality (Case Study: Jhono Garment, West Jakarta) - Anjar, Muhammad; Putro, Bramantiyo Eko (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2000)
Jhono Garment produces various kinds of clothing including t-shirts, polo, nightwear, children's clothes, sportswear, and others with a made by order system. The problem that is often experienced by this Garment is that there are still defects or defects in the product in the production process that cause cost and time losses. This study aims to determine the level of defects and sigma values of products produced by Jhono Garment, find out what waste factors must be eliminated first, find out the factors that cause product defects in Jhono Garment, provide recommendations for improvements to the causes of defects in Jhono Garment products. Data collection in this study is using primary and secondary data, namely production data from November 2022 to April 2023 and production process data. The methods used are lean six sigma, FMEA and fuzzy. The results showed that the sigma value of the Jhono Garment product is a T-shirt clothing product with a sigma value of 4.006. The waste factor that must be eliminated first is waste defects. The factors causing defects in Jhono Garment consist of 5 factors, namely humans, machines, materials, methods, and the environment. The recommendation for improvement of waste defects is to make folding molds in the product folding process.